From green to amber: is Australia's National Electricity Market signalling a financial warning for wind and solar power?. (August 2022) - Srianandarajah, Nesanthan; Wilson, Stephen J.; Chapman, Archie C.
Abstract: This paper examines the challenge of mobilising capital for renewable energy projects in Australia's National Electricity Market (NEM). Analysis of multi-year time series data by generation unit from the NEM identifies four factors that have reduced financial returns to existing variable renewable energy projects (VRE) and are adversely affecting the bankability of new projects. NEM curtailment of utility-scale solar PV grew to 4.7% in 2019/20 and 4.4% for wind power; with the number of VRE generators experiencing curtailment above 5% quadrupled from 7 to 29 from 2018/19 to 2019/20. Deteriorating marginal loss factors, with the number of generators assigned a MLF of 0.9 or lower tripling from 10 to 30, between 2017/18 to 2018/19, steadily increasing. Wholesale spot market price risk has increased markedly. Renewable Energy Certificates are in the ten-year plateau period to the legislated sunset of the federal Renewable Energy Target in 2030. The depressing effect of these factors is illustrated through financial analysis of an exemplar solar project. These findings have implications for goals for high to very high shares of wind and solar deployment in Australia and elsewhere; for investment risk, project financing structures, bankability of new generation; and market design, and regulation.